2011
DOI: 10.1080/09540121.2011.554526
|View full text |Cite
|
Sign up to set email alerts
|

HIV/STI prevention interventions targeting FSWs in China: a systematic literature review

Abstract: A rapid increase in heterosexual transmission of HIV and a high prevalence of sexually transmitted infections (STIs) in China signals potential outbreaks of generalized epidemics. A large proportion of heterosexual transmission has been through commercial sex; thus, millions of female sex workers (FSWs) and their clients play a critical role in the country's HIV/STI epidemics. A number of prevention interventions targeting FSWs have been implemented in response to changes in policy toward HIV as well as growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 39 publications
1
50
2
Order By: Relevance
“…The effect of these interventions needs to be evaluated in the future. Analysing the effects of interventions across varying FSW subgroup strata would offer a greater understanding of successful intervention elements 28. Especially, since knowledge alone may not translate necessarily into safe sex, particularly in the context of low literacy levels,29 strategies to increase HIV/STI risk perception and condom negotiation self-efficacy are urgently needed 30.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of these interventions needs to be evaluated in the future. Analysing the effects of interventions across varying FSW subgroup strata would offer a greater understanding of successful intervention elements 28. Especially, since knowledge alone may not translate necessarily into safe sex, particularly in the context of low literacy levels,29 strategies to increase HIV/STI risk perception and condom negotiation self-efficacy are urgently needed 30.…”
Section: Discussionmentioning
confidence: 99%
“…[141516] Approximately four million sex workers are present in China, which comprise a highly heterogeneous population that includes those from both low-end (ie, streets, beauty salons, roadside motels, and temporary sublets) and high-end venues (ie, karaoke clubs, massage parlors, night clubs, and hotels). [171819] Female sex workers (FSWs) play a critical role in the heterosexual transmission of HIV/sexually transmitted infections (STIs) in China. [19] Studies showed that the prevalence rate of syphilis among FSWs ranges from 9.5% to 15.8% in China.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 For FSWs in the community, community-based organizations may provide limited HIV interventions, subject to restraint from interference by the public security authorities. 11,12 FSWs work in various venues and are classified as high-, middle-, and low-tier according to the type of sex venue where they sell sex. 13 The sex work tier is often a key determinant of socio-economic status, work environment, type of client, and risk behavioural patterns of FSWs in China.…”
mentioning
confidence: 99%